2021
DOI: 10.1111/jocn.15830
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for establishing and sustaining clinical academic partnerships: A discursive review

Abstract: Aims and objectives To discuss the need for a formalised structure that bridges the clinical and academic realms with concrete recommendations for programme development. Background In the rapidly changing landscape of health care, nurses are challenged with the responsibility to engage in evidence‐based practice, quality improvement and research projects. Clinical and academic partnerships play a vital role in fostering collaboration, mentorship and resources. Design Discursive paper. Method Searching internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…18 Establishing a clinical-academic collaboration or partnership is a mutually beneficial key resource for supporting and promoting scientific nursing enquiry, overcoming clinician and academic barriers to engaging in scientific inquiry, and improving patient outcomes. 19…”
Section: Challenges To Establishing a Research Culturementioning
confidence: 99%
See 1 more Smart Citation
“…18 Establishing a clinical-academic collaboration or partnership is a mutually beneficial key resource for supporting and promoting scientific nursing enquiry, overcoming clinician and academic barriers to engaging in scientific inquiry, and improving patient outcomes. 19…”
Section: Challenges To Establishing a Research Culturementioning
confidence: 99%
“…Another important aspect is the participation of an academic facilitator or having access to research experts, 14,16,17 indeed in one study it was identified as the top facilitator 18 . Establishing a clinical‐academic collaboration or partnership is a mutually beneficial key resource for supporting and promoting scientific nursing enquiry, overcoming clinician and academic barriers to engaging in scientific inquiry, and improving patient outcomes 19 …”
Section: Challenges To Establishing a Research Culturementioning
confidence: 99%
“…Previous studies have confirmed the necessity and significance of academic-practice partnerships in nursing education and discipline development 13 14. Academic-practice partnerships that enhance education and research by sharing resources and specialties can be used to develop continuing education programmes and promote the generation and application of beneficial knowledge through joint planning and cooperation 12 15 16. Some literature also suggested that academic-practice partnerships had the potential to overcome some crucial barriers (eg, inadequate EBNP competence and training of clinical practice nurses, lack of patients and practice environments for academic nurses) to evidence-based practice by sharing resources and qualified personnel in clinical and academic settings 8 9 17…”
Section: Introductionmentioning
confidence: 97%
“…This search yielded seven reviews that focused on academic-practice partnerships in nursing. These reviews discussed the benefits, models, processes, structures and influencing factors in academic-practice partnerships in nursing education and/or research 11 15 17 21–23. However, there is a lack of reviews on academic-practice partnerships from the perspective of EBNP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation